Evaluating the Da'wah Safari Program Using the Kirkpatrick Model: Improving Islamic Character and Da'wah Skills in Primary Education - Hesti Kusumaningrum; Faizah Faizah; Salsabila Azahra; Sekar Puan Maharani; Imtiaz Sofiyanti; Jihan Zalika Rachman; Alif Rahman Hakim (AL-ISHLAH: Jurnal Pendidikan, 2025)
In response to the weakening of students’ Islamic character due to globalization and digital influences, Madrasah Ibtidaiyah Madinatunnajah implemented the Da'wah Safari program to strengthen students’ religious values and public speaking skills. This study evaluates the program’s effectiveness in improving students’ da’wah competencies and Islamic character using the Kirkpatrick evaluation model. A qualitative descriptive approach was employed, using the four-level Kirkpatrick model: reaction, learning, behavior, and results. Data were collected through interviews, observations, and document analysis involving seven informants, including school leaders, teachers, students, parents, and community members. Thematic analysis was conducted based on Miles, Huberman, and Saldaña's framework. Findings at the reaction level showed high student enthusiasm and satisfaction. At the learning level, students demonstrated improved understanding of Islamic teachings and da’wah techniques. Behavioral changes included increased discipline, confidence in public speaking, and consistent religious practice. At the results level, the program contributed to positive community engagement and enhanced the school’s public image. The Da'wah Safari program proved effective in fostering Islamic character and da’wah skills through experiential learning and community-based activities. The structured integration of religious content and public performance developed students’ moral behavior and communication abilities. While the use of digital media remains limited, this presents an opportunity for program development and wider dissemination in the future.